Ovatodiolide triggers ferroptosis in high-grade serous ovarian cancer through HMOX1 upregulation - Yew-Min Tzeng; Aye Aye Khine; Hsuan-Shun Huang; Tang-Yuan Chu (Molecular Therapy: Oncology)
High-grade serous ovarian carcinoma (HGSC) is the most aggressive and lethal gynecological malignancy, largely due to its asymptomatic early stages and late-stage diagnosis. Current standard treatments involve surgical resection combined with platinum-based chemotherapy, yet recurrence rates remain high, highlighting the urgent need for more effective therapeutic options. Ovatodiolide, a bioactive macrocyclic diterpenoid derived from traditional medicinal herbs, has been reported to possess anti-cancer properties against various malignancies. In this study, we demonstrated that ovatodiolide exerts potent cytotoxic effects on both HGSC cells and their precursor cells. RNA sequencing (RNA-seq) analysis reveals that the cytotoxicity of ovatodiolide is associated with the upregulation of heme oxygenase 1 (HMOX-1), along with the activation of oxidative stress and ferroptosis, suggesting a distinct cell death mechanism. These findings demonstrate that ovatodiolide induces HGSC cell death through a unique mode of action and highlight its potential as a promising therapeutic agent to complement or enhance existing treatment strategies.